Identification and critical appraisal of evidence for interventions for refractive error to support the development of the WHO package of eye care interventions: a systematic review of clinical practice guidelines. (21st February 2022) - Evans, Jennifer R; Lawrenson, John G; Ramke, Jacqueline; Virgili, Gianni; Gordon, Iris; Lingham, Gareth; Yasmin, Sumrana; Keel, Stuart
Abstract: Purpose: The World Health Organization is developing a Package of Eye Care Interventions (PECI) to support the integration of eye health care into national health programmes. Interventions included in the PECI should be based on robust evidence where available. Refractive error is a leading cause of blindness and vision impairment and is a PECI priority condition. The aim of this study was to provide high‐quality evidence to support the development of the PECI by identifying and critically appraising clinical practice guidelines (CPGs), and extracting recommendations for refractive error interventions. Methods: We searched for CPGs on refractive error published in the last 10 years. We conducted the searches initially in February and March 2019 and repeated them in March 2020. We evaluated the quality of potentially relevant guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool. Results: We identified 12 high‐quality CPGs relevant to refractive error, written by six organisations from three high‐income countries. Organisations used a variety of frameworks to assess the strength of recommendations based on available evidence, with the Grading of Recommendations Assessment, Development and Evaluation (GRADE) being most common. Vision screening for children aged 3 to 5 years was recommended consistently. Evidence for screening and eye evaluations at other ages was weaker, although ophthalmic professional organisations consistently recommended regular evaluations. Recommendations on optical and laser correction of refractive error were limited and did not consider implications for low resource settings. Interventions for slowing myopia progression in children were recommended, but these will need regular updating as new evidence emerges. Conclusions: Current high‐quality guidelines on refractive error have been formulated in high‐income countries. Recommendations focused on prevention and treatment of refractive error in low‐and middle‐income countries are lacking. Regular updating of systematic reviews and CPGs is essential to ensure that robust evidence is promptly appraised and incorporated into recommendations for eye health care practitioners.